Food sources of free sugars in children's diet and identification of lifestyle patterns associated with free sugars intake: the GRECO (Greek Childhood Obesity) study. Issue 13 (23rd November 2015) - Farajian, Paul; Risvas, Grigoris; Panagiotakos, Demosthenes B; Zampelas, Antonis
Abstract: Objective: Excessive free sugars consumption has a possible role in health issues, diet quality and obesity development. The present cross-sectional study aimed to identify the major food sources of free sugars in Greek children's diet and investigate possible associations of dietary patterns with free sugars intake. Design: Anthropometric measurements and information on dietary and physical activity habits were obtained. Energy and free sugars intake coming from foods were estimated and principal components analysis was applied to identify dietary patterns. Setting: The GRECO (Greek Childhood Obesity) study. Subjects: Nationwide sample of 3089 children (aged 10–12 years). Results: Adopting WHO criteria, 44·2 % of participants were categorized as having free sugars intake above 10 % of total energy intake. Mean contribution of free sugars to energy intake was 11·2 %, and the major food sources of free sugars differed from those of other childhood populations. Free sugars intake was not associated with overweight/obesity. Multiple linear regression analysis revealed that two lifestyle and dietary patterns, characterized by higher consumption of sweets, fast foods, fries, sugared drinks, frequently ordering/eating outside home and having meals in front of a screen (pattern 1) and higher consumption of whole fruits, 100 % fruit juices, vegetables, legumes and honey/jam (pattern 2), were positively associated with free sugars intake. Conclusions: A large proportion of children exceeded the recommended cut-off and free sugars intake was associated with lifestyle patterns rather than single foods. Public health programmes aiming to reduce free sugars consumption should be tailored on promoting the correct dietary habits of specific childhood populations.